O que se aprende na escola? representações sociais de adolescentes no ensino fundamental II - Magalhães, Nanci Araújo (2007)
This research has a objective to investigate the Social Representation that the adolescents construct about what they learn at school. Based on the principle that the Social Representations reflect the way that the individuals, the groups and the people construct their knowledge, interviewed teenagers that are in the last year of high school (8th grade) of the São Paulo city. The representations as they are supported in the social communication and based on the reality of the daily life, set up associations that become ourselves part of a group, making us able to observe a kind of social group carefully verifying what they think about determined object. The social representations are produced in the social relationships, and they are based on the beliefs and values of their family, media and school. The collaborators are 10 teenagers about 13 and 15 years. They are from different social-cultural groups of school: private and public. The investigation is on the same way of the qualitative research, combining the collection of data, by means of individual interviews guided by a central question - What do you learn at the school? It was used the technique of content analysis, proposed by Bardin. The research pointed out some subjects that give us the possibility to think about the practice as educators that are every day in the classroom with teenagers. They also reiterate the importance of considering the different social contexts that can promote different educational results, if they are not clear as objectives inside of an educational proposal.